Efficiency of silver nanoparticles against bacterial contaminants isolated from surface and ground water in Egypt - Dosoky, Reem; Kotb, Saber; Farghali, Mohamed (Journal of Advanced Veterinary and Animal Research, 2015)
The bactericidal efficiency of silver nanoparticles (AgNP) was evaluated against bacteria isolated from surface and ground water samples in Egypt. The AgNP were synthesized by typical one-step synthesis protocol, and were characterized using transmission electron microscopy and atomic absorption spectrophotometer. The bactericidal efficiency of AgNP was evaluated by its application in three concentrations i.e., 0.1, 0.05 and 0.01 ppm to water sample, and allowed to interact with bacteria for different duration e.g., 5 min 15 min, 30 min, 1 h and 2 h. Then, the bactericidal efficiency of AgNPs was determined by comparing the counted bacteria before and after the treatments. Higher mean values of total bacterial count (TBC), total coliform count (TCC), and total streptococcal count (TFS) were detected in surface water than in ground water. Also, the results showed that TBC, TCC and TFS exceeded permissible limits. Application of AgNP at different concentration, the number of bacteria in TBC was significantly reduced in all AgNP-exposed samples as compared to the control group (p<0.05). The highest concentration of AgNP exhibited highest bactericidal efficiency in TBC, where, after two hours, 0.1, 0.05 and 0.01 mg/L AgNP was found to be sufficient to inhibit 91.85, 89.14 and 74.92%, and 92.33, 85.23 and 53.17% in TBC of surface and ground water, respectively. Moreover, the inhibition efficiency of the highest concentration (0.1 ppm) against TCC reached to 98.10 and 99.88% in surface water and 95.54 and 99.20% in ground water after 1 h and 2 h, respectively. Similar results were found against TFS count. The AgNPs were found to be effective against bacteria of water origin. http://dx.doi.org/10.5455/javar.2015.b79